2011
DOI: 10.1051/alr/2011145
|View full text |Cite
|
Sign up to set email alerts
|

Age and growth of the smooth hammerhead shark,Sphyrna zygaena, in the Eastern Equatorial Atlantic Ocean, using vertebral sections

Abstract: -The smooth hammerhead shark Sphyrna zygaena (Sphyrnidae) is regularly caught as bycatch in pelagic longline fisheries, but is one of the least studied of all pelagic sharks. Recently, ICCAT (International Commission for the Conservation of Atlantic Tunas) issued recommendations underlining the need for more studies on the life history parameters of this and other pelagic shark species. To this end, the age and growth of S. zygaena were studied in the Eastern Equatorial Atlantic Ocean, in an area where growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 22 publications
1
18
0
5
Order By: Relevance
“…Regarding the staining method used, in which sections were stained with Crystal Violet solution, this stain had been successfully used in other shark species (e.g., Coelho et al, 2011;Fernandez-carvalho et al, 2011;Fernandez-Carvalho et al, 2015;Rosa et al, 2017), but never before used with blue sharks. For each vertebral sample one section was stained and the other was left unstained for comparison purposes, and it was concluded that the stained sections provided a higher contrast in the growth bands for the vast majority of the samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the staining method used, in which sections were stained with Crystal Violet solution, this stain had been successfully used in other shark species (e.g., Coelho et al, 2011;Fernandez-carvalho et al, 2011;Fernandez-Carvalho et al, 2015;Rosa et al, 2017), but never before used with blue sharks. For each vertebral sample one section was stained and the other was left unstained for comparison purposes, and it was concluded that the stained sections provided a higher contrast in the growth bands for the vast majority of the samples.…”
Section: Discussionmentioning
confidence: 99%
“…To enhance the band pattern, the sections obtained were stained with Crystal Violet solution (Sigma-Aldrich Co., St. Louis, MO), previously used in other shark ageing studies (e.g., Coelho et al, 2011;Fernandez-carvalho et al, 2011;Fernandez-Carvalho et al, 2015;Rosa et al, 2017), during 2 (for small sections) or 3 minutes (for bigger sections) on each side.…”
Section: Sample Processingmentioning
confidence: 99%
“…Smaller size classes can be accounted for by including known age-zero individuals (Bishop et al 2006) or back-calculation techniques (Smart et al 2013). However, one popular technique for correcting growth estimates for juvenile size classes is to fix the L 0 parameter to the empirical length-at-birth to adjust the model trajectory (Cailliet et al 2006;Coelho et al 2011). However, Pardo et al (2013) has demonstrated that the L 0 value of the VBGF-2 function is not equivalent to empirical length-atbirths as it lies outside the range of the data.…”
Section: Discussionmentioning
confidence: 99%
“…This occurred as models only converged on their true shape when sufficient data were available. However, one popular technique for correcting growth estimates for juvenile size classes is to fix the L 0 parameter to the empirical length-at-birth to adjust the model trajectory (Cailliet et al 2006;Coelho et al 2011). Growth models are most sensitive to data in the smallest and largest size classes of the growth curve (Haddon 2001).…”
Section: Gompertzmentioning
confidence: 99%
“…Por ende, los niveles de mercurio observados en los neonatos y juveniles en este estudio probablemente reflejan los de la madre (Adams et al 1999). Al crecer y hacerse adultos, estos tiburones disminuirían sus niveles de mercurio como resultado de una menor exposición y un crecimiento que diluiría las concentraciones de mercurio (Coelho et al 2011, de Penedo de Pinho et al 2001). …”
Section: Discussionunclassified